Lima tokoh IAIN Sunan Kalijaga Yogyakarta : diterbitkan dalam rangka temu alumni IAIN Sunan Kalijaga 24 - 25 September 2000 - Institut_Agama_Islam_Negeri (IAIN Sunan Kalijaga, 2000)
tr, c.1/stoc6, c.1/ws.c.2-3